The Cosmology of Love in the Qur'an: A Taoist-Sufistic Reading of Cosmic Verses through Sachiko Murata - Siti Masykuroh; M Masruchin (Universitas Muhammadiyah Surakarta, 2026)
Purpose - This article aims to examine the cosmology of love in the thought of Sachiko Murata and to explore its application to Qur'anic cosmic verses concerning the sky, the earth, and rain. While studies on Qur'anic cosmology and Murata's intellectual contributions have expanded considerably, limited attention has been given to integrating her Taoist-Sufistic framework into the interpretation of cosmic verses. The study argues that love (maḥabbah) constitutes an ontological foundation that underlies the structure and harmony of the cosmos. Design/methods/approach - This research employs a qualitative library-based methodology. Data were collected from primary and secondary sources related to Qur'anic cosmology, Sachiko Murata's writings, Taoist philosophy, and Islamic mysticism, particularly Ibn Arabi's metaphysics. The analysis utilizes thematic exegesis (tafsīr mawḍūʿī) combined with philosophical hermeneutics to uncover symbolic and relational meanings embedded in selected cosmic verses. Findings - The study reveals that the Qur'anic representation of the cosmos reflects a dynamic relational structure grounded in love. The sky symbolizes an active-transcendent principle, the earth embodies a receptive-immanent principle, and rain functions as a mediating element that animates their interaction. These cosmic relations illustrate maḥabbah as a unifying ontological force that sustains creation and cosmic order. Research implications/limitations - The study is limited to textual and philosophical analysis and does not incorporate empirical or ecological field data. Consequently, its conclusions are primarily interpretive and theoretical, providing a foundation for further interdisciplinary research on Qur'anic cosmology and environmental ethics. Originality/value - This article offers a novel integration of Murata's Taoist-Sufistic cosmology with Qur'anic studies and proposes a